2017
DOI: 10.1016/j.celrep.2017.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Control of Hpo/MST Kinase Activity through Autophosphorylation-Dependent Recruitment of the STRIPAK PP2A Phosphatase Complex

Abstract: The Hippo pathway controls organ size and tissue homeostasis through a kinase cascade leading from the Ste20-like kinase Hpo (MST1/2 in mammals) to the transcriptional coactivator Yki (YAP/TAZ in mammals). While previous studies have uncovered positive and negative regulators of Hpo/MST, how they are integrated to maintain signaling homeostasis remains poorly understood. Here we identify a self-restricting mechanism whereby autophosphorylation of an unstructured linker in Hpo/MST creates docking sites for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 46 publications
(83 reference statements)
9
91
0
Order By: Relevance
“…Both increased kinase activity and increased phosphorylation of the human Tricornered-like kinase were observed following treatment of COS-1 cells with okadaic acid (Millward et al, 1999). Subsequent studies of yeast and fly NDR kinases reported similar effects in response to okadaic acid treatment, indicating that negative regulation of NDR kinases by phosphatase activity is conserved from yeast to humans (Mah et al, 2001;Chan et al, 2005;Lai et al, 2005;Hergovich et al, 2006a;Koike-Kumagai et al, 2009;Zheng et al, 2017).…”
Section: The Stripak Complex Is a Negative Regulator Of Hippo Signalingmentioning
confidence: 91%
“…Both increased kinase activity and increased phosphorylation of the human Tricornered-like kinase were observed following treatment of COS-1 cells with okadaic acid (Millward et al, 1999). Subsequent studies of yeast and fly NDR kinases reported similar effects in response to okadaic acid treatment, indicating that negative regulation of NDR kinases by phosphatase activity is conserved from yeast to humans (Mah et al, 2001;Chan et al, 2005;Lai et al, 2005;Hergovich et al, 2006a;Koike-Kumagai et al, 2009;Zheng et al, 2017).…”
Section: The Stripak Complex Is a Negative Regulator Of Hippo Signalingmentioning
confidence: 91%
“…It is believed that the scaffolding proteins, including SLMAP, SIKE, STRIP1 (FAM40A), STRIP2 (FAM40B), direct and uphold PP2A/Striatin phosphatase specificity, and loss of these proteins consequently disassemble the STRIPAK complex; leading to hyper-phosphorylation of PP2A/Striatin target proteins. This is, for example, observed upon loss of SLMAP, which induces hyperphosphorylation of MST1/2 kinases (Bae et al, 2017;Zheng et al, 2017;Tang et al, 2019), while loss of STRIP1 induces hyper-phosphorylation of MST3/4 kinases (Madsen et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Over the past few years, extensive functional and mechanistic research has been conducted to resolve the framework of the Striatin Interacting Phosphatase and Kinase (STRIPAK) complex. The accumulated findings have linked specific components of the complex to various biological functions including vesicular trafficking (Zhang et al, 2013;Lant et al, 2015), Golgi assembly (Kean et al, 2011), Hippo signaling (Ribeiro et al, 2010;Zheng et al, 2017), autophagy (Huang et al, 2017), cell migration (Madsen et al, 2015;Bazzi et al, 2017), and cell cycle control (Cornils et al, 2011;Frost et al, 2012;Kazmierczak-Baranska et al, 2015;Pandey et al, 2017). Substantiated by these findings, the STRIPAK complex is supervising embryogenesis and development (Lant et al, 2015;Madsen et al, 2015;Sakuma et al, 2015Sakuma et al, , 2016Bazzi et al, 2017;Pal et al, 2017;Zheng et al, 2017), circadian rhythms (Andreazza et al, 2015), type 2 diabetes (Chursa et al, 2017), and progression of cancer (Wong et al, 2014;Zhang et al, 2014;Madsen et al, 2015;Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a protein phosphatase PP2A complex called STRIPAK (Bae et al, ; Praskova et al, ; Zheng et al, ), Dachsous–Fat system (Irvine & Harvey, ; Mao et al, ), and extracellular matrix (ECM) sensing integrins (Chakraborty & Hong, ; Dobrokhotov, Samsonov, Sokabe, & Hirata, ) are responsible for inactivation of the Hippo pathway. In high‐energy conditions, enzyme O‐GlcNac transferase deactivates Hippo signaling allowing the expression of YAP‐regulated growth‐promoting genes (Peng et al, ).…”
Section: Overview Of the Hippo Signaling Networkmentioning
confidence: 99%
“…In contrast, a protein phosphatase PP2A complex called STRIPAK (Bae et al, 2017;Praskova et al, 2004;Zheng et al, 2017), Dachsous-Fat system (Irvine & Harvey, 2015;Mao et al, 2006), and extracellular matrix (ECM) sensing integrins (Chakraborty & Hong, 2018;Dobrokhotov, Samsonov, Sokabe, & Hirata, 2018) by HIF-1α in hypoxic conditions (Xiang et al, 2015).…”
Section: Upstream Regulators Of the Hippo Pathwaymentioning
confidence: 99%